Fostering a productive educational environment: the roles of leadership, management practices, and teacher motivation - Sariakin Sariakin; Manovri Yeni; Musliadi Bin Usman; Aman Simare Mare; Munzir Munzir; Muhamad Saleh (Frontiers in Education)
This study explores the relationships between Principal’s Leadership, School Management Practices, Teacher Motivation, and Teacher Performance. This study uses a quantitative methodology and takes the form of the questionnaires as the data collection instrument. The teacher served as the focus of this investigation, while the leadership and administration skills of junior high school principals served as the study’s target. This study employed using Smart Partial Least Squares (PLS) to analyze how these factors interact and influence educational outcomes. The research employed Smart PLS to model and evaluate the complex relationships between these variables, highlighting the significant roles of leadership and management in shaping teacher effectiveness and overall school performance. The findings reveal that Principal’s Leadership significantly enhances both Teacher Motivation and Teacher Performance, underscoring the critical role of effective leadership in inspiring and improving teacher performance. In contrast, School Management Practices were found to significantly impact Teacher Performance but did not significantly affect Teacher Motivation, suggesting that management practices alone may be insufficient to boost motivation levels among teachers. Teacher Motivation was identified as a key driver of Teacher Performance, emphasizing that motivated teachers are more likely to perform at higher levels. The study advocates for a comprehensive approach that integrates strong leadership, effective management practices, and targeted strategies to enhance teacher motivation and performance. The research provides valuable insights and guidance for educators and administrators aiming to foster a productive educational environment.